Answer:
![\sum_(n=4)^(15)4(-3)^(n-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sbryzafra1kq36qylm7ejbezp01nlktk4n.png)
Explanation:
The given sequence is 4, -12, 36
We can see there is a common ratio
=
![(-12)/(4)=(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8x9hue3lf3b5o95bwt1959agdtgmz4l16v.png)
=
![(36)/(-12)=(-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/cwcui0ub8elxw23vb2lju7tekp8rtd6au6.png)
Therefore, the given sequence is a geometric sequence.
Now we have to determine the sigma notation of the sum for term 4 through term 15.
Since explicit formula of the sigma can be represented as
![T_(n)=a(r)^(n-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8uogtn2rxh6z0pz1gxw2p1cvfi6r80di2p.png)
where
= nth term
a = first term
n = number of term term
r = common ratio
and sum is denoted by
![\sum_(n=1)^(n)a(r)^(n-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d0u285bodgtqopxqsk7uttgzu7ighcmmys.png)
Now for the given sequence sigma notation will be
![\sum_(n=4)^(15)4(-3)^(n-1)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/sbryzafra1kq36qylm7ejbezp01nlktk4n.png)